The sialyltransferase ST3Gal-IV guides murine T-cell progenitors to the thymus - Sitte, Selina; Doehler, Daniela; Sperandio, Markus; Marth, Jamey D.; Vöhringer, David (Blood Advances, 2020)
T lymphocytes are important players in beneficial and detrimental immune responses. In contrast to other lymphocyte populations that develop in the bone marrow, T-cell precursors need to migrate to the thymus for further development. The interaction of P-selectin and P-selectin glycoprotein ligand-1 (PSGL-1) is crucial for thymic entry of T-cell precursors during settings of T-cell lineage reconstitution. PSGL-1 has to be sialylated to function as a ligand for P-selectin, and the sialyltransferase ST3Gal-IV might play a critical role in this process. We therefore investigated the role of ST3Gal-IV for T-cell development using competitive mixed bone marrow chimeric mice. We found that ST3Gal-IV is dispensable for homing and engraftment of hematopoietic precursors in the bone marrow. However, ST3Gal-IV deficiency affects seeding of the thymus by early T-cell progenitors, leading to impaired restoration of the peripheral T-cell compartment. This defect could be restored by ectopic retroviral expression of ST3Gal-IV in hematopoietic stem cells derived from ST3Gal-IV-deficient donor mice. Our findings show that ST3Gal-IV plays a critical and nonredundant role for efficient T-cell lineage reconstitution after bone marrow transplantation.
CRIS-Team WoS Importer:2020-05-29